How a "China-made" label influences Chinese Youth's product evaluation: The priming effect of patriotic and nationalistic news. (May 2022) - Yu, Anqi; Yu, Shubin; Liu, Huaming
Abstract: This study is to verify whether and how a "China-made" label can influence online consumers' product evaluation as adding labels to highlight products' attributes has become an acquainted measure online by e-tailers/firms to attract online consumers' attentions. For this purpose, we conduct a 2 (label of "China-made" vs. no label) x 3 (patriotism priming vs. nationalism priming vs. no priming) between-subject factorial design to verify hypotheses. The results reveal that when consumers' nationalism is primed, the label significantly enhances the product evaluation by increasing the perceived social value of the product. Priming consumers' patriotism, on the other hand, does not play a moderating role for this effect. A follow-up study confirms such effects for both low involvement and high involvement products. Therefore, e-tailers/firms that own China-made brands/products are advised to signal the "Chinese identity" of their products to online consumers under the current circumstance when nationalism and domestic brands are rising in China. The results also indicate that although products produced in a developing country are marked with a negative country of origin effect, marketers can turn it into a strength in marketing in certain conditions.